Numerical simulation on thermal‐hydraulic and thermoelectric characteristics of the TOPAZ‐II reactor core. (29th December 2020) - Dai, Zhiwen; Wang, Chenglong; Zhang, Dalin; Tian, Wenxi; Qiu, Suizheng; Su, G.H.
Summary: Numerical simulation of the Space Reactor Power System is of great importance to reactors development and application in aerospace. In this paper, thermal‐hydraulic and thermoelectric characteristics analysis based on 1/6th full thermionic reactor core of the TOPAZ‐II were performed using 3‐D computational fluid dynamics software STAR‐CCM + . A Benchmark study was conducted by comparing the numerical results with experimental data and design values with a maximum error of 5.4%‐11.8%. For the thermal‐hydraulic analysis: (a) the highest temperature point occurred at the center hole of the center thermionic fuel element (TFE) with the temperature of 2303 K; (b) the maximum temperature difference located in the fuel region and interelectrode gap with the value about 200 K and 1000 K, respectively; (c) axial temperature distribution of coolant is similar in each flow channel, and the maximum temperature difference appears at the reactor core outlet with the value of 10 K. For the thermoelectric analysis, the potential on center or the edge TFE is much higher or lower than the others, the calculated electrical power of the full thermionic reactor core is 4.95 kW, the distribution trend of current and potential is in a good agreement with the axial emitter temperature. Abstract : 3‐D full reactor core level thermoelectric and thermal‐hydraulic analysis of a thermionic reactor core has been investigated using CFD modeling. Electrical circuit model in the CFD simulation is developed based on the Rasor model. Benchmark study has been done by comparing the CFD calculation results with experimental data and design values in the literature with error of 5.4%‐11.8%.